Teacher’s Role: Implementation of Religious Character Education through the Habituation Method in Elementary School - Ailula Mufidatus Solihah; Ujang Sugara; Anang Fathoni (Universitas Pendidikan Ganesha, 2024)
Students' religious character is generally emphasized by PAI teachers, but in this case the class teacher has more awareness in forming character through habituation. This habit needs to be studied so that it can be an example for other schools in optimally forming religiosity. This research aims to analyze the implementation of religious character education through habituation in fourth grade elementary school students. This research uses a qualitative case study approach with the subjects being teachers, students and student guardians. Data collection was carried out through interviews, observation and documentation. The data analysis used is the Miles and Huberman model. The results of the research show that shaping students' religious character is the existence of habituation activities such as routine repetition and assistance in aqidah, morals and worship. Routine repetition of aqidah is carried out by praying before and after learning, and TPA activities. Implementation of routine repetition of worship is carried out by purifying and salat. Implementation of routine repetition of morals is carried out by behaving and speaking politely at all times and doing good deeds every Thursday. Implementation of aqidah assistance is carried out with cult guidance every Thursday morning and assistance in activities of believing in Allah and His Angels. Implementation of worship assistance is carried out with the practice of purification and assistance with congregational prayers such as sunnah and obligatory prayers as well as moral assistance including assistance in cultivating good character and counseling assistance.